# How would I solve the quadratic equation: 2x^2 + 6x = 0

I would factor out 2x to give

2(x+3)=0

2x^2 = -6x;

2x = -6;

x = -3.

hopefully thts the answer!

## To solve the quadratic equation 2x^2 + 6x = 0, you can follow these steps:

Step 1: Rewrite the equation in standard form, where one side is equal to zero:

2x^2 + 6x = 0

Step 2: Factor out the common factor from both terms, in this case, the common factor is 2x:

2x(x + 3) = 0

Step 3: Set each factor equal to zero and solve for x:

2x = 0 or x + 3 = 0

Step 4: Solve for x in each equation:

For 2x = 0, divide both sides by 2:

x = 0/2

Simplifying:

x = 0

For x + 3 = 0, subtract 3 from both sides:

x = -3

So, the solutions to the quadratic equation 2x^2 + 6x = 0 are x = 0 and x = -3.